In defense of self how the immune system really works - Clark, William R., 1938- (New York ; Oxford : Oxford University Press, 2008)
William Clark invites readers on a tour of the immune system introducing some of the most important medical advances and challenges of the past 100 years, from the development of vaccines and the treatment of allergies, automimmunity and cancer, to prolonging organ transplants and combating AIDS.
Description based on print version record.
Includes index.
Keywords: Immunology; Immunity; Immunologic diseases